Evaluating the effectiveness of palm oil certification in delivering multiple sustainability objectives. (12th June 2018) - Morgans, Courtney L; Meijaard, Erik; Santika, Truly; Law, Elizabeth; Budiharta, Sugeng; Ancrenaz, Marc; Wilson, Kerrie A
Abstract: Industrial oil palm plantations in South East Asia have caused significant biodiversity losses and perverse social outcomes. To address concerns over plantation practices and in an attempt to improve sustainability through market mechanisms, civil society organisations and industry representatives developed the Roundtable on Sustainable Palm Oil (RSPO) in 2004. The effectiveness of RSPO in improving the sustainability of the palm oil industry is frequently debated and to date, few quantitative analyses have been undertaken to assess how successful RSPO has been in delivering the social, economic and environmental sustainability outcomes it aims to address. With the palm oil industry continuing to expand in South East Asia and significant estates being planted in Africa and South America, this paper evaluates the effectiveness of RSPO plantations compared to non-certified plantations by assessing the relative performance of several key sustainability metrics compared to business as usual practices. Using Indonesian Borneo (Kalimantan) as a case study, a novel dataset of RSPO concessions was developed and causal analysis methodologies employed to evaluate the environmental, social and economic sustainability of the industry. No significant difference was found between certified and non-certified plantations for any of the sustainability metrics investigated, however positive economic trends including greater fresh fruit bunch yields were revealed. To achieve intended outcomes, RSPO principles and criteria are in need of substantial improvement and rigorous enforcement.